Household Shocks and Coping Strategies in Rural and Peri‐Urban South Africa: Baseline Data from the Size Study in Kwazulu‐Natal, South Africa. (7th April 2014) - Knight, Lucia; Roberts, Benjamin J.; Aber, J. Lawrence; Richter, Linda; ,
Abstract: The incidence and impact of a range of household shocks are investigated in a survey of households with children in 24 communities in peri‐urban and rural KwaZulu‐Natal, South Africa. The results highlight the importance of health shocks among households in a high HIV prevalence context. Economic shocks, in particular unexpected price increments for basic necessities, are widely reported and shown to have moderate to severe self‐rated impacts with possible long‐term cumulative, community‐wide effects. Behaviour‐based coping responses were the most common, especially reduced consumption and spending, which has the potential for negative impacts on the health developmental and well‐being of children. Copyright © 2014 John Wiley & Sons, Ltd.